Problematyka dostępu do danych zawartych w dokumentacji medycznej na gruncie obecnie obowiązujących przepisów administracyjnoprawnych - Szwejser, Diana (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
This article is about the medical documentation. For a long time medical care was rid of written form. Doctors treated their patient, but all doctor’s orders were verbally interacted. Medical documentation appeared later. For the present there isn’t legal definition of medical documentation. Analysis of this turn of phrase lead to ascertainment that medical documentation include all of medical information about treatment, medicaments, referrals. Medical documentation needs to be readable, contain accurate information, all entries should be in chronological order. It should have not only written form, but also an electronic form. Under the law, from the 1st of January, 2018 only an electronic form will be permissible. There are many people and public entities who are eligible to insight into medical documentation. The most important is patient. He can also entitle somebody to have insight into it. Empowerment is valid even if the patient dies.
Keywords: medical documentation; administrative law; medical law; patient’s rights; medical information